BIBLICAL FESTIVALS AND HINDU FEASTS - Nereparampil, Lucius (Journal of Dharma, 1990)
Feasts and celebrations keep the human spirit happy and elevated from the material level of man's existence and brings him somehow to the divine sphere. It is such celebrations that break the monotony of human life and give man a foretaste of heavenly bliss. They help man to acknowledge the break-through of a transcendent God in his history. and thereby to come in closer contact with that benevolent God.